Processes of Residential Differentiation in Socialist Cities - Sampo Ruoppila (European Journal of Spatial Development, 2004)
Abstract: This paper reviews the literature on the processes of residential differentiation in Budapest, Prague, Tallinn and Warsaw during the era of state socialism. It identifies the housing types that were part of the housing provision regime at different periods of the socialist era, and discusses the inequalities in access to them, examining how they affected the development of the socio-spatial pattern. The study finds that despite the egalitarian ideology of socialism, the socialist housing provision system produced several socio-occupational residential differentiations. Sometimes these were the direct result of projects conducted by the public sector itself; there were inequalities in access to public rental housing. Sometimes these were a result of the toleration of, or support for, differentiation in co-operative and owner-occupied housing. Furthermore, the study finds that there was continuity in the appreciation of some residential areas. Therefore, developments during socialism did not always challenge the capitalist past, but rather actually often continued its socio-spatial patterns, especially within inner city areas